Persistent primary thunderclap headache responsive to gabapentin - Garza, I. (Springer-Verlag, 2006)
We report the case of a woman with an apparent primary thunderclap headache which occurred frequently until she achieved a therapeutic dosage of gabapentin. Primary thunderclap headache is a rare type of headache that warrants significant testing to rule out more ominous possibilities. Whether gabapentin may help other primary thunderclap headache sufferers or not remains unclear. Further research is needed.